A test of the European Pleistocene refugial paradigm, using a Western Palaearctic endemic bird species. Issue 1889 (24th October 2018) - Drovetski, Sergei V.; Fadeev, Igor V.; Raković, Marko; Lopes, Ricardo J.; Boano, Giovanni; Pavia, Marco; Koblik, Evgeniy A.; Lohman, Yuriy V.; Red'kin, Yaroslav A.; Aghayan, Sargis A.; Reis, Sandra; Drovetskaya, Sofya S.; et al.
Abstract : Hewitt's paradigm for effects of Pleistocene glaciations on European populations assumes their isolation in peninsular refugia during glacial maxima, followed by re-colonization of broader Europe during interstadials. This paradigm is well supported by studies of poorly dispersing taxa, but highly dispersive birds have not been included. To test this paradigm, we use the dunnock ( Prunella modularis ), a Western Palaearctic endemic whose range includes all major European refugia. MtDNA gene tree, multilocus species tree and species delimitation analyses indicate the presence of three distinct lineages: one in the Iberian refugium, one in the Caucasus refugium, and one comprising the Italian and Balkan refugia and broader Europe. Our gene flow analysis suggests isolation of both the Iberian and Caucasus lineages but extensive exchange between Italy, the Balkans and broader Europe. Demographic stability could not be rejected for any refugial population, except the very recent expansion in the Caucasus. By contrast, northern European populations may have experienced two expansion periods. Iberia and Caucasus had much smaller historical populations than other populations. Although our results support the paradigm, in general, they also suggest that in highly dispersive taxa, isolation of neighbouring refugia was incomplete, resulting in large super-refugial populations.